Analysis of cerebral toxoplasmosis in a series of 170 allogeneic hematopoietic stem cell transplant patients. Issue 6 (18th September 2013) - Hakko, E.; Ozkan, H.A.; Karaman, K.; Gulbas, Z.
Abstract Introduction Cerebral toxoplasmosis is a rare but fatal complication in hematopoietic stem cell transplant patients, which mostly is caused by reactivation of latent disease. Methods In this study, we report an analysis of cerebral toxoplasmosis in a series of 170 allogeneic stem cell transplant patients during a 30‐month period at our institution. Results Among these allogeneic stem cell transplant patients, 5 were diagnosed with cerebral toxoplasmosis by brain magnetic resonance imaging and polymerase chain reaction of Toxoplasma gondii DNA. The incidence of cerebral toxoplasmosis was found to be 2.94%. Conclusion Mortality rate is known to be very high in cerebral toxoplasmosis; therefore, it is life saving to diagnose the disease in the early stages and start treatment promptly, especially in high‐endemic countries like Turkey.